1995
DOI: 10.1007/bf00175575
|View full text |Cite
|
Sign up to set email alerts
|

Glycoconjugates and keratin 18 define subsets of taste cells

Abstract: Sections of neonatal, normal adult and denervated adult rat tongue were examined with lectin histochemistry. Attention was focused upon intragemmal cells (cells within the taste bud) and the surrounding perigemmal cells. Informative staining patterns were observed with four of 12 lectins: Ulex europaeus (UEA-I), Bauhinia purpurea (BPA), Helix pomatia (HPA) and Lotus tetragonolobus (LTA) agglutinins. In normal adult tongues, BPA bound to those lingual epithelial cells lacking contact with the basal lamina. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
5
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
3
5
0
Order By: Relevance
“…Takami et al (1994) reported that the receptor cells of the olfactory epithelium and the vomeronasal organ differ from other epithelial cells of the nasal cavity in their glycoconjugate composition. Similar peculiarities have been reported for the receptor cells in the vestibular end organs (Takumida and Bagger-Sjöbäck 1991) and for those in the taste buds (Witt and Miller 1992;Zeng et al 1995). Interestingly, the taste bud receptors of rats contain high amounts of cytokeratin 18 (Zeng et al 1995) and thus further resemble the brush cells .…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Takami et al (1994) reported that the receptor cells of the olfactory epithelium and the vomeronasal organ differ from other epithelial cells of the nasal cavity in their glycoconjugate composition. Similar peculiarities have been reported for the receptor cells in the vestibular end organs (Takumida and Bagger-Sjöbäck 1991) and for those in the taste buds (Witt and Miller 1992;Zeng et al 1995). Interestingly, the taste bud receptors of rats contain high amounts of cytokeratin 18 (Zeng et al 1995) and thus further resemble the brush cells .…”
Section: Discussionsupporting
confidence: 78%
“…Similar peculiarities have been reported for the receptor cells in the vestibular end organs (Takumida and Bagger-Sjöbäck 1991) and for those in the taste buds (Witt and Miller 1992;Zeng et al 1995). Interestingly, the taste bud receptors of rats contain high amounts of cytokeratin 18 (Zeng et al 1995) and thus further resemble the brush cells . Although it has been demonstrated that brush cells of the trachea may directly contact afferent nerves (Luciano et al 1968), this is normally not the case for brush cells at other locations.…”
Section: Discussionsupporting
confidence: 78%
“…Since beta-N-acetylglucosamine is ubiquitously localized in all types of papillae in all mammals examined, it might play an essential role in the taste bud function. As for alpha-fucose, the present results positively correlated with the previous reports on the localizations of glycoconjugates in the rat [4], rabbit, frog and fish [3,4,[14][15][16][17][18]. In contrast, certain glycoconjugates were unique in some but not all types of papillae, such as alpha-N-acetylgalactosamine, alpha-mannose and alpha-D-glucose.…”
Section: Discussionsupporting
confidence: 91%
“…Based on the molecular structures of these receptors, it has been postulated that at least some of the receptors are glycoproteins, exposed to the extra-cellular surface of taste cells [7], and supposed to have a role in perceiving taste sensations. On the other hand, although several lectin histochemical studies have been reported until now, all of them reported only on a single species, such as rabbits [15], frogs [3] and teleost [16][17][18] and rats [4,14]; and no comparative studies have been made on different mammalian species in one report. In the present study, therefore, we lectin histochemically examined the cells of taste buds in the lingual papillae to determine and compare the types and compositions of glycoconjugates in five orders of mammalian species: artiodactyl, perissodactyl, rodent, carnivore and primate.…”
mentioning
confidence: 99%
“…Consistent with this idea is the expression of different glycoconjugates by distinct functional classes of cells in the visual (Chan et al, 1999), respiratory (Kasper and Singh, 1995;BurkhardtHolm, 1997;Dorscheid et al, 1999), gustatory (Zeng et al, 1995), olfactory (Taniguchi et al, 1993;Shnayder-Shapiro et al, 1995;Nakajima et al, 1998;, gastrointestinal (Sato and Spicer, 1982;Falk et al, 1994;Ge et al, 1998;Gebhard and Gebert, 1999;Poorkhalkali et al, 1999), reproductive (Zhou et al, 1994;Arenas et al, 1998;Romo et al, 1999), and immune (Clark et al, 1995;Sharma et al, 1996;Foster et al, 1998) systems in a variety of mammalian species.…”
Section: Discussionmentioning
confidence: 94%